Decalajul digital și excluziunea digitală a vârstnicilor în România - un studiu de caz în București-Ilfov - Dobre, Alexandra (Calitatea Vieții, 2022)
Romania becomes a fast ageing society. The support of the elderly became, consequently, a significant topic, and promoting digital technologies is an efficient modality to provide help in this regard. The lower degree of elderly digitalization must be understood in the context of multiple digital divides. Along with the existent divide between generations (age being one of the digital profficiency predictors), there are other factors too, with a major impact, as low level of education or revenues, these two being strongly correlated with a lower degree of digital technology use. This paper is examining the present situation of Internet use in a small sample of elder population in the region of Bucharest-Ilfov. The study analizes the causes that explain the lower digital abilities of eldelrly persons (over 65 years old), and the factors that influence these abilities, using data from Romanian society. The conclusions of the article find that public administration, the digital equipment manufacturers, and families of elderly persons should work together to help these persons to use the advantages of these new digital technologies.